Art, antiquities, and blockchain: new approaches to the restitution of cultural heritage. Issue 3 (16th April 2021) - Whitaker, Amy; Bracegirdle, Anne; de Menil, Susan; Gitlitz, Michelle Ann; Saltos, Lena
ABSTRACT: Objects of cultural heritage present a unique and important opportunity for the use of blockchain technology. Specifically, blockchain, a distributed ledger technology, can be used to disincentivize the sale of looted objects and to manage shared stewardship, ownership, and exhibition of these contested artifacts taken though war or colonialism. We offer background on repatriation of antiquities using the Byzantine Fresco Foundation as a core case study; introduce a working model of stakeholders in antiquities markets in both contemporary and historical context; and propose a blockchain solution using four different cases. The paper draws on newly sourced archival documents, game-theory interpretations of stakeholder behavior and application of this new technology in regulatory context. These blockchain applications are especially timely with the publication of the Sarr Savoy Report and the Arts Council England's rewriting of its restitution guidelines for museums and galleries.